Acute mycoplasma pneumoniae encephalitis in an adult - Leong, Wan Yi; Yusof Khan, Abdul Hanif Khan; Baharin, Janudin; Wei, Chao Loh; Abdul Rashid, Anna Misya’il; Wan Sulaiman, Wan Aliaa; Fan, Kee Hoo; Basri, Hamidon; Ahmad Apandi, Laila Mastura; Inche Mat, Liyana Najwa (Faculty of Medicine and Health Sciences, UPM, 2022)
Mycoplasma pneumonia is an atypical bacterium that causes mild respiratory tract infections, especially in the upper respiratory system. Mycoplasma pneumoniae infection is infrequently associated with various CNS manifestations such as encephalitis, meningoencephalitis, myelitis, Guillain-Barre syndrome and acute disseminated encephalomyelitis (ADEM). Here we report a rare case of mycoplasma encephalitis in an adult who presented with a first episode of seizure following fever and neck stiffness for one week. Mycoplasma pneumoniae antibody titer was markedly elevated at >1:320 and MRI brain revealed encephalitic changes with a lesion in the splenium. Interestingly, there was no associated respiratory infection and his stay in the hospital was also complicated by SIADH. The patient improved after treatment with a macrolide antibiotic.